PENGARUH METODE PEMBELAJARAN DAN KEMAMPUAN BERPIKIR KRITIS TERHADAP HASIL BELAJAR SEJARAH SISWA - Nashar Nashar (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2015)
This study aimed to determine the effect of learning methods and critical thinking skills toward the students’ outcomes in the learning of history. This research is quantitative research using treatment design by level 2x2.The research data was taken from the observation, tests and questionnaires. The results showed that (1) learning of the history’s outcomes of students using investigative group learning are better than learning of the history’s outcomes using conventional teaching methods, (2) there is interaction between learning method and critical thinking ability toward learning of the history’s outcomes of students; (3) learning of the history’s outcomes of students using learning methods investigation group with high critical thinking skills are better than learners who learn using conventional learning methods, (4) learning of the history’s outcomes of students using conventional teaching methods with low critical thinking skills are better than students using the investigative group learning method with the ability to think critically low.Theoretically, the results of this study can be used as a reference for developing teaching methods in teaching history in the high school. Furthermore, there is research that is expected to use different teaching methods with other independent variables that influence student learning of history’s outcomes.